2001
DOI: 10.1103/physrevb.63.033314
|View full text |Cite
|
Sign up to set email alerts
|

Quadruple-period ordering along [110] in aGaAs0.87Sb0.13alloy

Abstract: A quantitative structural model, based on x-ray diffraction, is provided to analyze quadruple-period atomic ordering along ͓110͔ in a GaAs 0.87 Sb 0.13 alloy grown on a ͑001͒ GaAs substrate by molecular beam epitaxy. To minimize the local strain energy derived by a valence force field ͑VFF͒ model for the alloy, atomic displacements were deduced and incorporated in our model. Calculation of the scattering pattern based on the model agrees well with experiment. We propose that this ordering originates from a (2ϫ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…On the atomic scale, the occupational defects are often randomly distributed, resulting in a reduction of the degree of ordering [5]. These defects can also exist on a larger scale, leading to antiphase domains [5,6]. The domain structure alters the phase of the scattered x-rays and consequently the peak position and intensity.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…On the atomic scale, the occupational defects are often randomly distributed, resulting in a reduction of the degree of ordering [5]. These defects can also exist on a larger scale, leading to antiphase domains [5,6]. The domain structure alters the phase of the scattered x-rays and consequently the peak position and intensity.…”
Section: Theoretical Approachmentioning
confidence: 99%
“…3,4 Ordering types including CuAu-I (L1 0 ), CuPt (L1 1 ), and chalcopyrite (E1 1 ) have been reported in GaAsSb for growth on a variety of substrates and crystallographic orientations. [9][10][11] The particular surface reconstruction is likely a factor in the growth process. [9][10][11] The particular surface reconstruction is likely a factor in the growth process.…”
mentioning
confidence: 99%
“…␦ i is a complex function of s and can be obtained independently from a valence force field ͑VFF͒ model calculation. 12,14 For CuPt-B ordered GaInP 2 , we found that the difference in length between the In-P and the Ga-P bonds is mainly accommodated by the displacement of P atoms. The displacement of In and Ga atoms is significantly smaller.…”
Section: Resultsmentioning
confidence: 96%
“…The method can be extended to other types of ordering in semiconductor alloys, e.g., triple-and quadrupleperiod ordered systems where modulation of the peak intensity due to atomic displacements has been observed by both x-ray diffraction 14 …”
Section: Discussionmentioning
confidence: 97%